Global prescribed-time stabilization via time-scale transformation for switched nonlinear systems subject to switching rational powers - Yao, Hejun; Gao, Fangzheng; Huang, Jiacai; Wu, Yuqiang (Applied mathematics and computation, 2021)
•Fully taking into consideration of practical system requirements, global prescribed-time stabilization problem of SNSs is firstly considered.•A novel time-scale transformation is recommended to change the original nonsingular prescribed-time stabilization problem into the finite-time stabilization problem of transformed time-varying one.•Under the weaker restricted condition on characterizing system growth, a systematic design method of common coordinate transformation is proposed by delicately utilizing CLF-based-AOPI technique.•As an application of the proposed theoretical result, the problem of prescribed-time control of a liquid-level system is solved. This paper is concerned with the problem of global prescribed-time stabilization for a kind of uncertain switched nonlinear systems (SNSs) in p-normal form. Notably, the significant features of the study are that, the system under investigation possesses the switching rational powers, and the system states are driven to zero in prescribed finite time. A novel time-scale transformation is recommended which can change the original nonsingular prescribed-time stabilization problem into the finite-time stabilization problem of converted time-varying system. On basis of this, a new framework of studying state feedback stabilization within prescribed-time of SNSs is established with the aid of the common lyapunov function-based adding one power integrator (CLF-based-AOPI) technique. For arbitrary switchings, it is showed that the states of the closed-loop system (CLS) are rendered to zero in prescribed finite time. Simulation example of a liquid-level system is presented to confirm the effectiveness of the given control approach.